2014
DOI: 10.1021/jm5001908
|View full text |Cite
|
Sign up to set email alerts
|

4-Amino-1-hydroxy-2-oxo-1,8-naphthyridine-Containing Compounds Having High Potency against Raltegravir-Resistant Integrase Mutants of HIV-1

Abstract: There are currently three HIV-1 integrase (IN) strand transfer inhibitors (INSTIs) approved by the FDA for the treatment of AIDS. However, the emergence of drug-resistant mutants emphasizes the need to develop additional agents that have improved efficacies against the existent resistant mutants. As reported herein, we modified our recently disclosed 1-hydroxy-2-oxo-1,2-dihydro-1,8-naphthyridine-3-carboxamides IN inhibitors to develop compounds that have improved efficacies against recombinant IN in biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 31 publications
5
56
0
Order By: Relevance
“…A 2D ligand interaction of molecule 5sS [14] is displayed in Figure 11. It represents the interaction of the molecule with the surrounding amino acids of 1BIS.pdb within an 8-Å radius.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2D ligand interaction of molecule 5sS [14] is displayed in Figure 11. It represents the interaction of the molecule with the surrounding amino acids of 1BIS.pdb within an 8-Å radius.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 5 and Figure 6 (generated using ICM-Pro, Molsoft L.L.C.) represent an example of a drug-like [14] and nondrug-like molecule [14], respectively. The molecules were docked into the active site of 1BIS.pdb [9] and are shown in the potential binding site pocket identified by ICM-Pro.…”
Section: Drug-like and Nondrug-like Molecules/inhibitorsmentioning
confidence: 99%
“…Further investigations indicated that incorporation of free amine and alkylamines at the C‐4 position of 2‐naphthyridinone fragment was favorable to the activity, while arylamines were disfavored. The relative contribution order was free amine > alkylamines > arylamines . In particular, compound 6o (EC 50 : 1.1–35 nM) (Figure ) was highly active against IN wt and mutants (Y143R, N155H, R263K, G118R, and G140S/Q148H), and it was 1.4‐64.8 folds more potent than the reference raltegravir against all tested HIV‐1 IN.…”
Section: ‐Quinolone Derivativesmentioning
confidence: 98%
“…Besides IN, RT, and PR are also essential for HIV replication. Therefore, RT and PR have also been used as targets by anti‐HIV therapeutics . 2‐Quinolone derivatives 7 (Figure ) exhibited promising inhibitory activity against wt (IC 50 : 0.24–0.71 µM) and mutant HIV‐1 RT (Cys181 and Il100, IC 50 : 0.86–2.50 µM), which were comparable to nevirapin (IC 50 : 0.30 µM) against wt RT, but >40‐fold more active than nevirapin (IC 50 : > 100 µM) against mutant HIV‐1 Cys181 and Il100 RT .…”
Section: ‐Quinolone Derivativesmentioning
confidence: 99%
“…Zhao et al [91,92] synthesize bicyclic inhibitors having a hydroxyl group at position 1 and 4 in 1, 8-naphthyridine-3-carboxamide scaffolds and evaluate their HIV1 integrase inhibitory activity. Amongst these amides, N-(2,4-difluorophenyl)-1-hydroxyl substituted 1, 8-naphthyridine-3-carboxamide (80a) and N-(2,4-difluorophenyl)-1,4-dihydroxyl substituted 1, 8-naphthyridine-3-carboxamide (80b) show antiviral activity in nanomolar range potencies against HIV-1 integrase.…”
Section: Anti-hiv Activitymentioning
confidence: 99%